(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In India,until the eighties, potassium did not gain much consideration on the groundsthat of the general conviction that Indian soils were overall supplied withpotassium. In actuality, trim evacuation of potassium frequently equivalents orsurpasses that of nitrogen.